Investigation of the Effect of Dimensional Characteristics of Stone Column on Load-Bearing Capacity and Consolidation Time - Mohammad Reza Mohtasham; Mahdi Khodaparast (Salehan Institute of Higher Education, 2018)
One of the best methods for rehabilitating loos and soft soils is the application of stone columns. This method enhances the soil properties by increasing its load-bearing capacity, decreasing the soil subsidence, and accelerating the consolidation rate. In the present paper, numerical analysis of a stone column of 10 m in length into a clayey soil using ABAQUS software is presented. The stone column was modelled based on the concept of unit cell, i.e. a single stone column with the surrounding soil. In this respect, material of the stone column was modelled using the elastoplastic behavioural model of Mohr-Coulomb, while Cam Clay behavioural model was used for the surrounding clayey soil. Furthermore, throughout the analyses performed in this study, effects of different parameters (e.g. applied load on rigid foundation, and the stone column length and diameter) on the subsidence and consolidation time of the rigid foundation were examined. The results indicated that, construction of a stone column into clayey soil decreases the subsidence and consolidation time of the soil considerably. In additions, increases in length and diameter of the stone column were found to significantly contribute to reduced subsidence and consolidation time of soil.